8 The effect of replenishing kidney yang medicine on gynecological diseases. (19th December 2016) - Tian, Shuo; Miao, Mingsan; Bai, Ming; Xiang, Liling; Lou, Xin
Abstract : Objectives: To study the effect of replenishing kidney yang medicine on the prevention and treatment of gynecological disease, and provide a reference for further clinical studies. Methods: A comprehensive literature search was conducted to determine the effect of replenishing kidney yang medicine on the prevention and treatment of gynecological diseases, in order to understand current research and development, and provide a reference for clinical treatment. Results: The study has found that most replenishing kidney yang medicine has an estrogenic effect, such as the traditional Chinese medicines Epimedium, Antler, Eucommia, Psoralea, Dodder, Cnidium, Cistanche deserticola and Astragalus complanatus, and traditional Chinese patent medicine such as Guilingji capsules, Erxian decoction, Bushen Huoxue prescription and Yougui pills. Replenishing kidney yang medicine is often used to treat female disease such as perimenopausal syndrome, polycystic ovary syndrome, uterine hypoplasia, kidney deficiency type of infrequent menstruation, breast hyperplasia, kidney deficiency caused by ovulation disorders, premature ovarian failure and perimenopausal osteoporosis, and has a good therapeutic effect. Conclusions: Replenishing kidney yang medicine has a good therapeutic effect for the treatment of gynecological diseases, but the mechanism of drug action as it relates to the etiology and pathogenesis of these diseases has not yet been clearly elucidated. Therefore we recommend in-depth scientific clinical observation to determine the effect of replenishing kidney yang medicine on gynecological diseases so that better treatment programs can be developed. Acknowledgments: This research was financially supported by the National 'Eleventh Five-Year' Support Program (Grant No. 2008BAI53B09), Henan Province Outstanding Scientific and Technological Innovation Team (Grant No. TCJ2014-391) and Zhengzhou Municipal Science and Technology Innovation Team Program (Grant No. 131PCXTD612).